Związki frazeologiczne identyczne oraz podobne formalnie w językach indonezyjskim i polskim - Wiatrowski, Przemysław (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2018)
The article discusses Indonesian and Polish phraseological units, and specifically fixed expressions (idioms) and formulaic expressions (phrasemes). The linguistic units considered come predominantly from Indonesian and Polish dictionaries of phrases. The research also aims to provide a thorough description of such phraseological units characterized by either identical or similar formal structures between the compared languages. Particular focus is placed on identicality or similarity in qualitative and/or quantitative terms. The formally identical phraseological units include expressions having the same number of components arranged in the same order in the expression’s structure and having units with meanings having the same non-phraseological use. The formally similar phraseological units display certain lexical and grammatical qualitative and/or quantitative differences.